2012
DOI: 10.1021/jm300126x
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel DFG-Out RAF/Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) Inhibitors. 1. Exploration of [5,6]-Fused Bicyclic Scaffolds

Abstract: To develop RAF/VEGFR2 inhibitors that bind to the inactive DFG-out conformation, we conducted structure-based drug design using the X-ray cocrystal structures of BRAF, starting from an imidazo[1,2-b]pyridazine derivative. We designed various [5,6]-fused bicyclic scaffolds (ring A, 1-6) possessing an anilide group that forms two hydrogen bond interactions with Cys532. Stabilizing the planarity of this anilide and the nitrogen atom on the six-membered ring of the scaffold was critical for enhancing BRAF inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…Some examples of BTA derivatives acting as agonists or antagonists of various receptors and enzymes are as follows- b-Arrestin-biased dopamine D2 receptor [287] 4 Vascular endothelial growth factor receptor 2 (VEGFR2) inhibitors [288] 5 Apurinic/apyrimidinicendonuclease 1 inhibitors [289] 6…”
Section: Bta Asenzyme and Receptor Agonists/antagonistsmentioning
confidence: 99%
“…Some examples of BTA derivatives acting as agonists or antagonists of various receptors and enzymes are as follows- b-Arrestin-biased dopamine D2 receptor [287] 4 Vascular endothelial growth factor receptor 2 (VEGFR2) inhibitors [288] 5 Apurinic/apyrimidinicendonuclease 1 inhibitors [289] 6…”
Section: Bta Asenzyme and Receptor Agonists/antagonistsmentioning
confidence: 99%
“…[48] Okaniwa and co-workersd eveloped derivatives of sorafenib (10)a sd ual inhibitors of BRAF(V600E) and VEGFR2 kinases for the treatment of varioush uman cancers. [49] The synthesis involved the hydrolysis of ethyl ester 57,f ollowed by Curtius rearrangement of the carboxylic acid in the presence of tert-butanol to give the Boc-protected amine. The Boc group was then deprotected to afford the 2-aminoimidazo[1,2-b]pyridazine derivative 58,w hich was then acylated to afford 59 (Scheme 15).…”
Section: Kinase and Phosphatase Inhibitorsmentioning
confidence: 99%
“…Okaniwa et al. () designed 27 inhibitors that have various [5,6] fused bicyclic scaffolds to target the DFG‐out state of VEGFR2 and found a promising inhibitor. Weimin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Oguro et al (2010) identified one extremely potent compound targeting the DFG-out state of VEGFR2 by designing 30 novel pyrimidine derivatives. Okaniwa et al (2012) designed 27 inhibitors that have various [5,6] fused bicyclic scaffolds to target the DFG-out state of VEGFR2 and found a promising inhibitor. Weimin et al (2014) designed and synthesized a series of bis-aryl F I G U R E 1 (a) Structure of LEN-VEGFR2 in DFG-in state (PDB code: 3WZD), (b) structure of SOR-VEGFR2 in DFG-out state (PDB code: 3WZE); the G loop, the αC helix, and the A-loop were respectively shown in green-, purple-, and blue-colored cartoons, (c) chemical structures of the three drugs, LEN, SOR, and SUN [Colour figure can be viewed at wileyonlinelibrary.com] urea and bis-aryl amide derivates to bind to the DFG-out state of B-Raf V600E /VEGFR2, and one of them showed similarly equivalent antitumor efficacy in vivo, compared to Sorafenib.…”
Section: Introductionmentioning
confidence: 99%